The Effect of Migration on Urbanization of Turkey, Case of Diyarbakir - M. Oguz Sinemillioglu; Nurtekin Ozen (European Regional Science Association (ERSA), 2006)
The study will be deal with migration, which is a very important phenomenon in urbanization process and mostly has negative effects and brings lots of problems to urban life. Migration could be describe as a movement that contains demand for a better life, i.e. demand for housing, demand for job, demand for school, etc… This demand, however, puts out of order urban life and disintegrates the urban system. In Turkey, especially after 1950ies, there is migration and sometimes this migration has been containing very big numbers in terms of population. Besides, after 1990ies, Southeastern Anatolia Region of Turkey has given out migration, especially via the city of Diyarbakir. The migration, from the city and the region to west side of Turkey, like Istanbul, Ankara and Izmir, used Diyarbakir as a stopover. In addition of being a stopover point, Diyarbakir not only gives out migration but also get in migration. Thus makes Diyarbakir a city that has no history in social life and in urban culture. Shortly, The study will try to question migration and its effects to Turkey's urbanization process in Diyarbakir case.
Keywords: 330